Islamic Religious Education and the Challenges of Religious Moderation in Multicultural Society - Riyanto (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
Islamic Religious Education (IRE) plays a strategic role in instilling the values of religious moderation within plural and dynamic multicultural societies. This study aims to analyze the role of Islamic Religious Education in addressing the challenges of religious moderation and to identify practical strategies for its implementation in multicultural contexts. The research employs a library research method with a descriptive qualitative approach oriented toward practical implementation. Data were obtained from various literature sources, including books, scholarly journal articles, previous research findings, and policy documents relevant to Islamic Religious Education and religious moderation. Data analysis was conducted using content analysis techniques by examining patterns, challenges, and strategies for implementing religious moderation in IRE learning. The findings indicate that the implementation of religious moderation in Islamic Religious Education continues to face several challenges, including textual religious understanding, the influence of digital media that disseminates extreme narratives, limitations in curriculum and instructional materials, and uneven readiness among IRE teachers. Nevertheless, this study finds that practical strategies such as contextual learning approaches, dialogical learning, integration of national values, and strengthening teacher role modeling can serve as effective solutions in fostering moderate attitudes. This research affirms that Islamic Religious Education plays a crucial role in developing tolerant, inclusive, and harmonious attitudes within multicultural societies.